Effects of nano-(Pr₆O₁₁,CeO₂) addition and Pr, Ce doping in Bi-2223 superconductor - Ahmad Nizar, Nur Amalina Hafza (2013)
The effect of doping and addition of Pr and Ce in Bi-2223 system sintered at 850 ⁰C for 48 hours were investigated by X-ray diffraction techniques (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and critical temperature measurement. Bi1.6Pb0.4Sr2Ca2-xPrxCu3Oδ and Bi1.6Pb0.4Sr2Ca2-xCexCu3Oδ with x=0.00-0.10; (Bi1.6Pb0.4Sr2Ca2Cu3Oδ)1-x(nano Pr6O11) and (Bi1.6Pb0.4Sr2Ca2Cu3Oδ)1-x(nano CeO2) with x=0.00 - 0.03 were prepared by solid state reaction method. The phase purity, lattice parameters, superconducting properties, surface morphology and grain size were found to be dependen on Pr and Ce concentration in the sample. The XRD results patterns show that all Pr and Ce samples contain 2212 peaks which correspond to the low-superconducting phase. The intensity of these peaks increases towards higher value, as the Pr and Ce concentration increases. The volume of high 2223 phase decreases gradually as the Pr and Ce concentration increases. The lattice parameters calculated from XRD data show a slight decrease in the c-axis while a-axis increase with the increase of Pr and Ce concentration. The scanning electron microscopy viewing shows platelets like-grain for all samples which is a signature of high 2223 and low 2212 phases. The elemental analysis by EDX measurement of sample reveals the existence of Pr and Ce that are homogeneously distributed in BSCCO matrix. The chemical formula of sample elements composition that has been estimated from EDX measurements is in good approximation to that Bi2223 system with noticeable excess in oxygen ratio which may be due to the existence of Pr and Ce in sample. The study shows that Pr and Ce do not improve the Tc of BSCCO system. This is due to the existence of low 2212 phase which weakened the coupling of grains.